2023
DOI: 10.1021/acsami.3c06317
|View full text |Cite
|
Sign up to set email alerts
|

Surface Conversion of ZnO Tetrapods Produces Pinhole-Free ZIF-8 Layers for Selective and Sensitive H2 Sensing Even in Pure Methane

Mirjam P. M. Poschmann,
Leonard Siebert,
Cristian Lupan
et al.

Abstract: As the necessary transition to a supply of renewable energy moves forward rapidly, hydrogen (H2) becomes increasingly important as a green chemical energy carrier. The manifold applications associated with the use of hydrogen in the energy sector require sensor materials that can efficiently detect H2 in small quantities and in gas mixtures. As a possible candidate, we here present a metal–organic framework (MOF, namely ZIF-8) functionalized metal-oxide gas sensor (MOS, namely ZnO). The gas sensor is based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In this work, Poschmann et al pointed out the use of ZnO nanoparticles in polycrystalline powder form and the conductivity hindrance effect of the ZnO–MOF–ZnO sequenced sensing material morphology. 228 Thus, they used the tetrapodal single-crystalline ZnO microparticles to avoid this undesired conductivity reduction. The ZIF-8 layer over the single-crystalline ZnO microparticles provides excellent selectivity towards the H 2 molecules, even in the presence of optimum methane concentration.…”
Section: Chemiresistive Gas Sensing Of Porous Materialsmentioning
confidence: 99%
“…In this work, Poschmann et al pointed out the use of ZnO nanoparticles in polycrystalline powder form and the conductivity hindrance effect of the ZnO–MOF–ZnO sequenced sensing material morphology. 228 Thus, they used the tetrapodal single-crystalline ZnO microparticles to avoid this undesired conductivity reduction. The ZIF-8 layer over the single-crystalline ZnO microparticles provides excellent selectivity towards the H 2 molecules, even in the presence of optimum methane concentration.…”
Section: Chemiresistive Gas Sensing Of Porous Materialsmentioning
confidence: 99%
“…Significant advancements have been made so far toward the fabrication of MOF-based chemiresistive sensors with salient sensing performance towards a series of analytes. 12–21 For example, Zhang et al demonstrated excellent selectivity of sensors based on ZnO@ZIF-8 core–shell structures toward H 2 prepared using homogeneous precipitation and screen-printing techniques. 13 Similarly, Stock et al obtained ZnO@ZIF-8 composites with outstanding selectivity toward H 2 through ZnO transformation.…”
Section: Introductionmentioning
confidence: 99%
“…13 Similarly, Stock et al obtained ZnO@ZIF-8 composites with outstanding selectivity toward H 2 through ZnO transformation. 14 Additionally, Long et al prepared ZnO@ZIF-8 core–shell nanorod films, while Jung et al developed PMMA/ZIF-8 bilayers as molecular sieving layer with strong resistance to CO interference in H 2 detection. 15,16 Furthermore, Mao et al fabricated flexible field-effect transistor (FET) sensors based on the in situ growth of Ni 3 (HHTP) 2 , which exhibited high sensitivity to NO 2 at room temperature (with a detection limit of 56 ppb) and excellent selectivity.…”
Section: Introductionmentioning
confidence: 99%